Dasar-Dasar Pendidikan Islam Dalam Perspektif Al-Qur’an Dan Hadis - Nuh, Husaini; Habib, Muhammad Ammar; Zahrani, Muthiah (Journal of Sustainable Education, 2025)
Islamic education is firmly grounded in the Qur’an and Hadith as the two primary sources of Islamic teachings. The urgency of this study lies in the importance of understanding the foundational principles of Islamic education in order to develop an educational system that aligns with Islamic values and remains relevant in a changing world. This study aims to identify and analyze the fundamental principles of Islamic education as reflected in the Qur’an and Hadith. The research method employed is qualitative-descriptive with a library research approach, in which data is collected through the examination of Qur’anic verses and hadiths related to education. The results indicate that the foundations of Islamic education include tawhid as the primary basis, the importance of knowledge, noble character, the habituation of worship, and social responsibility. The Qur’an and Hadith not only provide normative guidance but also offer pedagogical principles that are applicable in educational processes. This study emphasizes that Islamic education is holistic, encompassing intellectual, spiritual, moral, and social aspects in an integrated manner.